2020
DOI: 10.9734/ajraf/2020/v6i230101
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Variety Improvement for Climate Resilience

Abstract: High temperature stress unfavorably affects plant growth and reduces grain yield (GY). This study was conducted with an aim to identify the terminal heat tolerance of one hundred and two wheat genotypes with three checks. They were sown under normal (non-stress) and late (stress) conditions at Regional Agricultural Research Station (RARS), Tarahara; RARS, Nepalgunj and National Wheat Research Program (NWRP), Bhairahawa, Nepal. The trial was sown in Augmented design during 2014/15 winter season as a Nepal heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…2), indicating genotype selection based on the tested tolerance indices can be an effective tool for identifying droughttolerant wheat genotypes. Many researchers have also reported similar results while testing the same tolerance indices singly or in a group (Singh et al, 2011;Bennani et al, 2017;Kamrani et al, 2017;Puri et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…2), indicating genotype selection based on the tested tolerance indices can be an effective tool for identifying droughttolerant wheat genotypes. Many researchers have also reported similar results while testing the same tolerance indices singly or in a group (Singh et al, 2011;Bennani et al, 2017;Kamrani et al, 2017;Puri et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…While genotypes with a high value of PC2 and a low value of PC1 are low-yielding genotypes under stress conditions i.e., SVIN-312, IR-192077-21-21-3-B, and IR10L192 which had relatively low performance under both conditions. Kamrani et al (2018) and Puri et al (2020) reported similar results while evaluating durum wheat and spring wheat genotypes for heat stress tolerance, respectively. A positive and significant correlation between STI, GMP, and MP with Yp and Ys has also been previously reported by other researchers (Abdolshahi et al, 2013;Carvalho et al, 2022;Hussain et al, 2021;Pavithra and Vengadessan, 2020;Garg and Bhattacharya, 2017;Ullah and Shakeel, 2019), which further supports our findings.…”
Section: Correlation and Principal Component Analysismentioning
confidence: 66%
“…Stress tolerance indices were calculated based on yield under late sown and drought under late sown condition. STIs had been used to identify stress-tolerant genotypes of wheat (Puri et al, 2020;Sharma et al, 2013;Singh et al, 2011). TOL, MP, GMP, YSI, STI, MSTI1, MSTI2, and SSI were www.cornous.com used to evaluate the stress tolerance of tested genotypes (Bennani et al, 2017;P.…”
Section: Yield Performancementioning
confidence: 99%